A New Dawn : Rethinking Sovereign ESG - Gratcheva, Ekaterina M.; Gurhy, Bryan; Emery, Teal; Wang, Dieter; Oganes, Luis; Linzie, Jarrad K.; Harvey, Lydia; Marney, Katherine; Murray, Jessica; Rink, Rupert (World Bank, Washington, DC, 2021)
Environmental, social, and governance (ESG) investing is quickly becoming ordre du jour in sovereign debt investing. There remains, however, lack of clarity around frameworks for scoring sovereign ESG performance, industry practices, and the definition of sustainability itself. This World Bank publication consists of two independent reports. The first part is written by the World Bank and takes stock of the current sovereign ESG investing framework and proposes improvements. The second part presents a survey on ESG practices among emerging market (EM) sovereign debt investors conducted by J.P. Morgan (JPM), which launched the first EM sovereign ESG index in 2018. This publication is a result of the World Bank's proactive engagement with stakeholders on pertinent sovereign ESG issues and is part of a publication series under the auspices of the Global Program on Sustainability (GPS).